Learning through the Looking Glass : Anticipation through the Lens of Social and Transformative Learning at a Futures literacy Lab - Richards, Martyn (My University, 2022)
The emergent phenomena of a complex world produce novel situations and opportunities that are difficult to prepare or plan for. Futures Literacy is proposed as a participatory transformative practice for developing capabilities that help individuals to both sense, and make sense of, novelty, through anticipation for emergence. This dissertation contributes to the empirical basis of how engaging in critical self-reflection as a collective, produces valuable insights into how assumptions form the lenses through which we imagine times later than now. The learnings that occur when individuals encounter simulated emergence in a challenging but supportive and creative environment, and the products of that process in terms of concrete actions, are contextualised within Futures Literacy learning journeys. This dissertation explores the role of transformative learning for understanding the social learning that occurs at a Futures Literacy Laboratory (FLL) through analysis of participant experiences and reflections using the Wenger-Trayner value creation framework. This study articulates that learning through anticipation for emergence is characterised by complexity, impredicavity, and reflexivity, which requires a broad range of cognitive and emotional skills to navigate. Participants of an FLL who are open to the process encounter deeply challenging critiques and insights that come to be understood as significant steps in understanding the inner sources of anticipatory assumptions. If these can then be explored under conditions of psychological safety, then alternative lenses become available that allow for the enhanced perception of the emerging present as well as their own boundaries. This process is cognitively and emotionally demanding and contingent on enabling factors and initial conditions. Weaving the participant experiences of this event into a broader narrative of learning provides opens opportunities for individual insights and practice, but also opportunities for new avenues of research. The results indicate that there is positive evidence that FLLs provoke reconsideration of established assumptions and can foster new lines of thinking. Situating FLLs as Transformative and social learning spaces, allows for the identification of practical implications and the generation of learning narratives than contribute to our understanding of the change processes at play in Futures Literacy capability building.
Keywords: Futures Literacy, Anticipation Studies, Transformative Learning, Social Learning, Wenger-Trayner Value Creation Framework, Futures Literacy Laboratory